Efektivitas Berbagai Produk Fungi Mikoriza Arbuskula Dalam Meningkatkan Produktivitas Stylosanthes guianensis Pada Tanah Masam: The Effectiveness of Various Arbuscular Mycorrhizal Fungi Products in Increasing Productivity of Stylosanthes guianensis on Acid Soil - Agam Rizki; Panca Dewi Manu Hara Karti; I Prihantoro (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
This study aimed to evaluate the effectiveness of Arbuscular Mycorrhizal Fungi (AMF) against Stylosanthes guianensis plants on acid soils. The research was conducted in the greenhouse of the Agrostology Laboratory of IPB. The research design used was a completely randomized design with 5 treatments and 8 replications, treatments were different types of AMF, without AMF (F0), commercial AMF (FU), AMF product IPB 1 (EM1), AMF product IPB 2 (EM2) and AMF product IPB 3 (EM3). AMF was given as much as 20 grams per planting hole. The given fertilizers were manure and NPK fertilizer. The treatment without AMF was given 100% of the recommended dose, while treatment with AMF was only given 50% of the dose. The results showed that there was no significant difference between treatments on growth variables (plant height, number of trifoliate leaves, number of branches, stem diameter and leaf chlorophyll). The type of AMF affected the fresh shoot production, and the highest was at EM1 (38.03 grams), as well as the number of root infections had a significant effect, and the highest production was at EM1 (77%). The conclusion in this study was that the use of AMF could reduce the use of manure and NPK 50% from the recommended dose, could increase the growth and productivity of Stylosanthes guianensis on acid soils and AMF product IPB 1(EM1) gave the best results. Key words: root infection, marginal soil, leguminous, Stylosanthes guianensis